Kemampuan Literasi Informasi Mahasiswa Prodi Perpustakaan dan Ilmu Informasi Angkatan 2021 UIN Malang dalam Menyelesaikan Tugas Perkuliahan dengan Model Literasi Big Six - Qomariyah, Hartia Wahidatul; Lestari, Rizki Yuni; Puspita, Anindya Gita (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Students as academics in higher education need information to carry out assignments given by lecturers. Student interaction with information is certainly different from one another. This study was written to describe the information literacy abilities of students majoring in Library and Information Sciences at UIN Malang. The information literacy model used in this research framework is the big six literacy model. The method used is a qualitative approach and data collection techniques using interviews. The results of the study show that each student has different information literacy skills in completing their coursework. Several stages of information literacy that students have mastered are task definition, use of information, and synthesis. However, there are still stages that need to be improved, such as information search strategy, location and access to information, and evaluation